THE COMPARATIVE ANALYSIS OF ECOLOGICAL INDICATORS - Bikova E.V. (Problems of the Regional Energetics)
The comparative analysis of ecological indicators designed and specified for Moldova and similar indicators of the countries of CIS is made in the work. Some general items of information about power systems of the countries of CIS (the established capacities, manufacture of the electric power) are given, the analysis of dynamics of emissions GHG- СО2, NOx, SO2 in Moldova and comparison with the emissions level in other countries of CIS is made.